Vers l'institutionnalisation de l'enseignement autonomisant – La technologie, soutien et obstacle à l'innovation - Anne Chateau; Sophie Bailly; Maud Ciekanski (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
A project of language learning digital platform for Lansad (Languages for Specialists of Other Disciplines) learners and teachers is under development at the University of Lorraine (UL) (Chateau & Bailly, 2013). The objective is to disseminate several autonomizing schemes developed over the last years (Bailly et al., 2008; Chateau & Zumbihl, 2012 ; Carette, Guély & Pereiro, 2011).Our article will use a few examples to show how these experimental schemes used digital tools to favor the empowerment of learners. The positive feedback of teachers and learners involved in these schemes naturally produced the necessity to go beyond the experimental phase and to reach progressive institutionalization, via a digital platform project. But this institutionalization has proved problematic. Obstacles and incentives that occurred during the development of the platform will be identified, through the answers to two questionnaires sent to all university language teachers. It is often said that technical innovation does not necessarily lead to educational innovation. This study tries to clarify the relationships between these two types of innovation.